Human histone genes map to multiple chromosomes. - Tripputi, P (1986)
Histone genes were mapped to at least three human chromosomes by Southern blot analysis of DNAs from a series of mouse-human somatic cell hybrids (using 32P-labeled cloned human histone DNA as probes). Chromosome assignment was confirmed by in situ hybridization of radiolabeled histone gene probes (3H-labeled) to metaphase chromosomes. One human histone gene cluster (lambda HHG41) containing an H3 and H4 gene resides only on chromosome 1, whereas other clusters containing core (H3, H4, H2A, and H2B) alone (lambda HHG17) or core together with H1 histone genes (lambda HHG415) have been assigned to chromosomes 1, 6, and 12. These results suggest that the multigene family of histone coding sequences that reside in a series of clusters may be derived from a single cluster containing one each of the genes for the five principal classes of histone proteins. During the course of evolution, a set of events, probably involving reduplication, sequence modification, and recombination, resulted in the present pattern of human histone gene distribution among several chromosomes.